Investigation of bedrock at the hilly area using common array profiling spectral analysis of surface waves method - Ramli, Ahmad Bukhari; Norinah, A. R.; Taib, Aizat; Hasbollah, D. Z. A.; Ismail, Norfarah Nadia; Bawadi, Nur Faizah (Books & Journals Private Ltd., 2021)
Locating hard layers or bedrock is particularly important in deep subsurface exploration. However, due to the scale effect of conventional testing, it is sometimes difficult to provide a greater overview of the subsurface conditions. This motivates a method that is capable of providing better resolution to a certain depth. This paper presents an investigation of bedrock using a nondestructive method at the hilly area as a supportive method to the existing borehole. The borehole recorded granite at respectively at 25 and 24m. CAP-SASW method that is employed successfully mapping the interested area. The result showed that the granite is considered as a slightly weathered rock with shear wave velocity ranging from 850-1600 m/s.